Identification, structural modification, and dichotomous effects on human immunodeficiency virus type 1 (HIV-1) replication of ingenane esters from Euphorbia kansui - Liu, Qingbo; Li, Wei; Huang, Li; Asada, Yoshihisa; Morris-Natschke, Susan L.; Chen, Chin-Ho; Lee, Kuo-Hsiung; Koike, Kazuo (European journal of medicinal chemistry, 2018)
Euphorbia kansui showed potent anti-HIV-1 activity during screening of a library composed of plant extracts from Euphorbiaceae and Thymelaeaceae families. Bioassay-guided isolation led to identification of ingenane esters as the active compounds. Further chemical modification resulted in 3-(2-naphthoyl)ingenol (23), which exhibited the most potent anti-HIV-1 activity. Compound 23 also acted as an HIV-1-latency-reversing agent on activation of HIV-1 replication in a latently infected U1 cell model and a T cell latent HIV-1 model JLat-A2. [Display omitted] •MeOH extract of Euphorbia kansui showed potent anti-HIV-1 activity.•Ingenane esters from Euphorbia kansui are potent anti-HIV-1 agents.•Naphthoyl group at C-3 of 20-deoxyingenol and ingenol enhanced anti-HIV-1 activity.•3-(2-Naphthoyl)ingenol is a potent HIV-1 latency reversing agent.